MAIN PROVISIONS OF THE QUALITY CONCEPT PERSON-ORIENTED EDUCATION (Pedagogy of Higher and Secondary Education, 2004)
The article deals with the problems of personality-oriented education as well as the possibility of realization of the main criterion of quality of education.